Color and state of maturity of fruit of the husk tomato. - Benito-Bautista, Pedro (2015)
The present study aimed to identify the physical and chemical characteristics that determine the state of maturity of the fruit of four varieties of husk tomato. One hundred fruits of the varieties: San Martin, Tecozautla 04, Rendidora, and Diamante, were collected. They were cultivated at a density of 40,000 plants/ha under experimental greenhouse conditions at the Interdisciplinary Research Center for Integrated Regional Development (CIIDIR), National Polytechnic Institute (IPN), in Oaxaca, Mexico. The plants were grown during the summer-autumn 2013 and spring-summer 2014 growing cycles. The husk filling and elapsed time since the fruit set were considered as indicators of harvest. Fruits were stored at room temperature (25 ± 3 °C), and each week 10 fruits of each variety were selected and analyzed for weight loss, penetration resistance, soluble solids, color, pH and titratable acidity. The statistic results indicate that color parameters a*, h * and color index (IC), were significantly high, and showed a high correlation with the physical and chemical properties for the state of maturation. The a* color coordinate presented the highest coefficient of correlation with fruit texture, followed by IC and h*. At the same time, a * and CI showed strong correlation with variables weight loss, titratable acidity, pH, and soluble solids. According to these results, the a* color parameter showed the greatest correlation with quality features, and varieties Tecozautla 04 and San Martin had the best quality characteristics.